2021
DOI: 10.2147/rru.s277482
|View full text |Cite
|
Sign up to set email alerts
|

GreenLight Laser™ Photovaporization versus Transurethral Resection of the Prostate: A Systematic Review and Meta-Analysis

Abstract: GreenLight laser™ photovaporization of the prostate (GLL-PVP) has become a valid alternative to traditional transurethral resection of the prostate (TURP) in men requiring surgery for benign prostatic hyperplasia. We aimed to review systematically the safety and efficacy of studies comparing GLL PVP and TURP in the medium-term. A comprehensive literature search was performed. Twelve studies were identified for meta-analysis. Meta-analyses showed a longer postoperative catheterization time (risk ratio (RR): 1.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…One limitation is the challenge of completely vaporizing the transition zone in large-volume prostates. Although prostates > 80 ml can be treated with PVP, these cases are associated with a long operative time, extra fibers, and a high reoperation rate due to incomplete vaporization [3][4][5]. Moreover, there are no pathological specimens after PVP, which may lead to missed diagnosis of prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…One limitation is the challenge of completely vaporizing the transition zone in large-volume prostates. Although prostates > 80 ml can be treated with PVP, these cases are associated with a long operative time, extra fibers, and a high reoperation rate due to incomplete vaporization [3][4][5]. Moreover, there are no pathological specimens after PVP, which may lead to missed diagnosis of prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…One study showed that the postoperative catheter insertion time and hospital stay were shorter and the risk of blood transfusion was lower in the PVP group compared to TURP, but the risk of dyspareunia and reoperation rates were higher in the PVP group, and there was no difference in the risk of urinary tract infection or risk of postoperative re-catheterisation between the two groups. Whereas in the postoperative follow-up included (IPSS, QoL, Qmax and PVR), the improvement in IPSS after TURP surgery was better than PVP in the early versus mid-term (2-year follow-up results), while QoL and Qmax were not significantly different, and PVR improved better than TURP after PVP surgery, and the 5th year follow-up showed that: the results of IPSS, QoL and Qmax TURP was better after surgery, while PVR was not significantly different between the two groups [9]. Lai et al showed that in perioperative terms (including bleeding-related transfusion, TUR syndrome, perforation of the peritoneum, clot retention, urinary tract infection and acute urinary retention), PVP had a lower incidence of transfusion, RR = 0.14 (p < 0.01) and clot retention (RR = 0.14, p < 0.01), TUR syndrome (RR = 0.19, p < 0.01) and perforation of the peritoneum ( RR = 0.09, p < 0.01) were lower, but PVP had a higher risk of mild to moderate voiding difficulties (RR = 1.76, 95% CI 1.17 to 2.65, p < 0.01), and there was no significant difference between PVP and TURP in terms of long-term complications (including bladder neck contracture, retrograde ejaculation, urethral stricture) [10].…”
Section: Green Lasermentioning
confidence: 79%
“…Most studies reported shorter hospitalization durations with PVP, ThuVARP, DiLEP, and HoLEP than with TURP [ 24 , 25 , 26 , 27 ]. Some smaller studies reported no significant differences in hospitalization duration between HoLEP and B-TURP [ 25 , 28 ].…”
Section: Discussionmentioning
confidence: 99%